THE EXTRACTION OF DRIED LEMONGRASS (CYMBOPOGON CITRATUS) WITH DISTILLED WATER AS A REPELLENT TO REDUCE DISEASES CAUSED BY BITES OF MOSQUITOES (CULICIDAE) IN INDONESIA - Ibnu Najib; Retno Nur Fauziah; Khairunnisa Arrachman (Universitas Muhammadiyah Semarang, 2017)
Indonesia is a country that has the diversity of plants that can be used as one source of essential oils (Feriyanto,2013). Lemongrass oil in the health field can be used as an anticeptic, anti- inflamation, analgetik, and sedative(Giuliani and Satuhu, 2012)Lemongrass can be used for the treatment and can be utilized as an ingredient of SOAP, insect repellent, as well as aroma therapy. Essential oil from lemongrass herbs can be obtained by means of presses. In addition, Lemongrass scented myrrh essential oil can be obtained by means of distillation.The principle of distillation is to isolate or separate two or more component liquid based on the boiling point ofwater distillation methods, these materials then will be distilled directly with boiling water, as the result, thematerial will float above the water or submerged completely (Sastrohamidjojo, 2004). The results of the distillation is generally in the form of essential oils containing rough water, the necessary process for withdrawal of water from the essential oil so that the quality of essential oils will improve and the color will become more clear. Method of withdrawal of water using sodium sulfate (Na2SO4) anhydrous, where water will be pulled by the anhydrous Na2SO4 to produce essential oils with high purity. After obtained essential oils with a high concentration of manufacturing process is done, then a lotion will be blended with essential oils as well as some sweet scent, in order to get the anti mosquitos lotion in essential oil. Keywords: Lemongrass oil, Essensial oil of herba serai, Distillation.